PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2017 - Risdiyati; Tjahjani Murdijaningsih; Minadi Wijaya (Majalah Imiah Manajemen & Bisnis, 2020)
This study examines the effect of profitability on the stock prices of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. In general, this study aims to examine the effect of profitability ratios on stock prices. The profitability ratio in this study is proxied by Return On Assets (ROA), Net Profit Margin (NPM) and Earning Per Share (EPS), while stock prices in this study use stock prices after the audit report. The population in this study were all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period 2015-2017 as many as 37 companies. The research sample used purposive sampling method. Based on predetermined criteria, obtained as many as 12 companies used as research samples. The analytical method used is multiple regression. The results of the study stated that during the years 2015-2017 (1) Based on the F test the model was declared feasible (2) Based on the t test ROA had a significant positive effect on stock prices, NPM had no significant negative effect on stock prices and EPS had a significant positive effect on stock prices (3 ) The coefficient of determination (R²) of 0.657, which means that the independent variable that affects the dependent variable is 65.7% and the remaining 34.3% is influenced by other variables outside of this study